PENGARUH PEMBERIAN POC LIMBAH JERAMI PADI TERHADAP PERTUMBUHAN BIBIT KOPI ROBUSTA (Coffea canephora) PADA MEDIA ALUVIAL - Andre Anto; Venti Jatsiyah; Beny Setiawan (Politeknik Negeri Ketapang, 2025)
Coffee is a plantation commodity with significant economic value in Indonesia and globally. Efforts to increase nutrient availability and improve the chemical properties of alluvial soil require the addition of liquid organic fertilizer made from rice straw waste. This study aimed to determine the effect of applying liquid organic fertilizer (POC) made from rice straw waste on the growth of Robusta coffee seedlings in alluvial soil.This study used a non-factorial completely randomized design (CRD) consisting of five treatments. Each treatment had five replications, resulting in 25 experimental units, each consisting of three plant samples, for a total of 75 samples. The treatments were: K0: No POC Application, K1: Concentration 200 mL/L, K2: Concentration 250 mL/L, K3: Concentration 300 mL/L, and K4: Concentration 350 mL/L. The data were analyzed statistically using Analysis of Variance (ANOVA). If a significant effect was found, the Duncan Multiple Range Test (DMRT) was used at the 5% level. Rice straw waste organic fertilizer (POC) at a concentration of 250 mL was the best for increasing leaf number, root length, and plant dry weight. Rice straw waste organic fertilizer at a concentration of 300 mL was the best for increasing plant height and leaf width. Meanwhile, rice straw waste organic fertilizer at a concentration of 350 mL was the best for increasing stem diameter.